The Implementation of Student Discipline Character through School and Parents' Collaboration - Syaikhoni, Yusuf; Subandi, Subandi; Fadillah, Kharis; Pratiwi, Wiwied; Wulandari, Wulandari (CV. Creative Tugu Pena, 2021)
A person who has a disciplined attitude will reflect through obedient. obedient and orderly behavior with a feeling of responsibility for what has become the rules he has received. In reality, discipline seems hard for some people to do, it covers all aspects of discipline. Tujuan penelitian ini adalah menganalisis faktor-faktor yang melatarbelakangi minimnya karakter disiplin siswa di SMP Islam Cendikia Darussalam dan menganalisis bentuk kerjasama sekolah dan orang tua di SMP Islam Cendikia Darussalam The method used in this research is a qualitative approach, the methods that are usually used are interviews, observation, and document. Qualitative descriptive in this study is used to develop a theory that is built through data obtained in the field. The factors that influence students, thats is parenting styles in daily life, social relationships, and self-understanding. The forms of cooperation that exist are cooperation and socialize school rules, form school and parent / guardian cooperation organizations, school committees, home visits, receive visits from parents of guardians, collaborate in groups, and carry out counseling guidance at schools. Efforts are made through collaboration, namely carrying out deliberations with guardian parents, learning the character of discipline from an early age which is carried out jointly between teachers and schools, internalizing disciplinary values ??in subjects, building a conducive school environment in various ways including those equipped with school infrastructure, holding positive activities that build character values ??of students, control, rewards and punishments, and modeling. Keywords: Learning Caracters, Disciplined Attitude, Collaboration School